Stimulation of macrophage phagocytosis and lymphocyte count by exogenous prolactin administration in silver sea bream (Sparus sarba) adapted to hyper- and hypo-osmotic salinities - Narnaware, Yuwaraj; Kelly, Scott; Woo, Norman (My University, 1998)
Juvenile silver sea bream (Sparus sarba) were adapted to hyper- (33 ppt) and hypo-osmotic (6 ppt) salinities for 3 weeks and injected daily with ovine prolactin (1 μg/g body weight i.p.) during the last 7 days of the adaptation period. Fish injected with prolactin exhibited significant increases in percent phagocytosis and phagocytic index of both pronephric and splenic macrophages regardless of salinity. Prolactin injection also resulted in elevated blood lymphocyte counts in both hyper- and hypo-osmotically adapted sea bream. The present results provide further evidence for the existence of a neuroendocrine–immune link in teleosts.
Keywords: macrophage phagocytosis; prolactin; sea bream; salinity; nonspecific immunity